1994
DOI: 10.1063/1.356583
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of n-type dry thermally oxidized 6H-SiC metal-oxide-semiconductor diodes by quasistatic and high-frequency capacitance versus voltage and capacitance transient techniques

Abstract: Dry-oxidized n-type 6H-SiC metal-oxide-semiconductor capacitors are investigated using quasistatic capacitance versus voltage (C-V), high-frequency C-V, and pulsed high-frequency capacitance transient (C-r) analysis over the temperature range from 297 to 573 K. The quasistatic C-V characteristics presented are the first reported for 6H-SiC MOS capacitors, and exhibit startling nonidealities due to nonequilibrium conditions that arise from the fact that the recombination/ generation process in 6H-SiC is extraor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
11
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 12 publications
3
11
1
Order By: Relevance
“…Compared with the former UV illumination measurement, the C -V curves in the latter UV illumination measurement show no great changes except a slight increase in inversion capacitance. The results measured under UV illumination are similar to the work of Neudeck et al 4 with a difference that we did not observe appreciable hysteresis. C -V measurements for NO and N 2 O annealed MOS capacitors gave similar results.…”
Section: ͓S0003-6951͑97͒04415-x͔supporting
confidence: 93%
“…Compared with the former UV illumination measurement, the C -V curves in the latter UV illumination measurement show no great changes except a slight increase in inversion capacitance. The results measured under UV illumination are similar to the work of Neudeck et al 4 with a difference that we did not observe appreciable hysteresis. C -V measurements for NO and N 2 O annealed MOS capacitors gave similar results.…”
Section: ͓S0003-6951͑97͒04415-x͔supporting
confidence: 93%
“…The shift of the Fermi level away from the bottom of the semiconductor conduction band must then have the effect of causing the emission rate to be less than the rate of change of the gate charge 15 even at 573 K as evidenced by the observed hysteresis effects. These results are in marked contrast to those reported for n-type 6H-SiC͑0001͒ MOS structures, 13 which show no appreciable hysteresis, and a shift in the C -V curves to more positive gate voltages as the temperature is increased from 300 to 573 K. This shift indicates that in this case, more charge is trapped at the interface due presumably to a larger number of slow traps being thermally excited. 13 It should also be mentioned that depth profiles of impurities in the AlN layer determined by secondary ion mass spectrometry revealed that about 10 19 cm Ϫ3 oxygen atoms were introduced into the layer during growth; 16 but the drift of such impurity ions under the applied electric fields and at the low temperatures used here is not expected.…”
contrasting
confidence: 89%
“…The C -V curve shows deep depletion for negative gate voltages with no inversion capacitance characteristics observed due to the extremely low minority-carrier generation rate. 13 However, hysteresis appears in this portion of the curve consistent with the presence of slow interface traps that cannot follow the change in the gate bias in our experiment. Illumination during the initial biasing of the device in deep depletion results in a reduction of the charge occupancy of these interface traps.…”
supporting
confidence: 66%
“…The curved parts near the origins follow the usual pattern observed in Si when the capacitance approaches its equilibrium level . The far-end parts of the plots, that are due to the field-enhanced emission from interface traps [16], [17], show strong increases that are similar to the behavior observed by Neudeck et al for dry oxides on 6H SiC [21]. The increases are (6) and (8), to enable extrapolations to room temperature.…”
Section: A Minority-carrier Lifetime and Surface-recombination Velocitysupporting
confidence: 51%